Follicular growth and atresia at the time of oocyte aspiration differentially affect in vitro embryo production in mares - Thadeu de Castro; Alejandro de la Fuente; Kazuki Takahashi; Katarzyna Malin; Soledad Martin-Pelaez; Paulo Sérgio Gomes; Victória Ferreira Gurian; Matheus de Castro Azevedo; Lauren Riley Ofer; Erin L. Oberhaus; Eduardo L. Gastal; Carlos Ramires Neto; et al. (Theriogenology, 2026)

Environmental quality assessment in urban nature reserves from Ushuaia (Tierra del Fuego, Argentina): towards a sustainable urban management - Amalia Lara Bursztyn Fuentes; Melisa Martínez; Magali Jazmin Castillo; Nicolás Ojeda; Camila Tarantino; Micaela Morella; Adrián Ayala; Soledad Lorena Diodato (Sustainable Water Resources Management, 2026)

From clinic to lab: Sperm parameters for equine in vitro embryo production - Soledad Martin-Pelaez; Morgan Orsolini; Margo Verstraete; Alejandro de la Fuente; Kazuki Takahashi; Stuart Meyers; Pouya Dini (Journal of Equine Veterinary Science, 2026)

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

IVF with frozen-thawed sperm after prolonged capacitation yields comparable results to ICSI in horses: A morphokinetics study - Soledad Martin-Pelaez; Alejandro de la Fuente; Kazuki Takahashi; Itzel Tirado Perez; Jazmin Orozco; Carolina T.C. Okada; Carlos Ramires Neto; Stuart Meyers; Pouya Dini (Theriogenology, 2025)

High-pressure pulses for Aspergillus niger spore inactivation in a model pharmaceutical lipid emulsion - Estefanía Brito-Bazán; Gabriel Ascanio; Maricarmen Iñiguez-Moreno; Montserrat Calderón-Santoyo; Maria Soledad Córdova-Aguilar; Edmundo Brito-de la Fuente; Juan Arturo Ragazzo-Sánchez (International Journal of Food Microbiology, 2023)

Effect of pentobarbital as a euthanasia agent on equine in vitro embryo production - Soledad Martin-Pelaez; Zachary Rabow; Alejandro de la Fuente; Peyton Draheim; Alan Loynachan; Oliver Fiehn; Stuart Meyers; Candace Lyman; Pouya Dini (Theriogenology, 2023)

Molecular effect of holding equine oocytes: a road to cytoplasmic maturation? - Soledad Martin-Pelaez; Alejandro De la Fuente; Machteld van Heule; Stuart Meyers; Pouya Dini (Journal of Equine Veterinary Science, 2023)

Environmental response of arbuscular mycorrhizal fungi under soybean cultivation at a regional scale - Valeria Soledad Faggioli; Fernanda Covacevich; Gabriel Grilli; Claudio Lorenzon; Bethania Aimetta; Monica Sagadin; Adrián Langarica-Fuentes; Marta Noemí Cabello (Mycorrhiza, 2022)

Organophosphorus pesticide mixture removal from environmental matrices by a soil Streptomyces mixed culture - Gabriela Briceño; Karen Vergara; Heidi Schalchli; Graciela Palma; Gonzalo Tortella; María Soledad Fuentes; María Cristina Diez (Environmental Science and Pollution Research, 2018)

S treptomyces genus as biotechnological tool for pesticide degradation in polluted systems - Gabriela Briceño; María Soledad Fuentes; Juliana María Saez; María Cristina Diez; Claudia Susana Benimeli (Critical Reviews in Environmental Science and Technology, 2018)

Silicon Deficiency Induces Alkaline Phosphatase Enzyme Activity in Cultures of Four Marine Diatoms - Soledad Fuentes; Gary H. Wikfors; Shannon Meseck (Estuaries and Coasts, 2014)

Phylogeography of the shrimp Palaemon floridanus (Crustacea: Caridea: Palaemonidae): a partial test of meta‐population genetic structure in the wider Caribbean - Juan Antonio Baeza; Maria Soledad Fuentes (Marine Ecology, 2013)
Marine organisms with a pelagic stage are often assumed to display minor population structure given their extended larval development and subsequent high long‐distance dispersal ability. Nonetheless, considerable population structure might still occur in species with high dispersal ability due to current oceanographic and/or historical processes. Specifically, for the wider Caribbean and Gulf of Mexico, theoretical and empirical considerations suggest that populations inhabiting each of the following areas should be genetically distinct: Panama, Belize, Southwest Florida (Tampa), and Southeast Florida (Fort Pierce). This study tests the hypothesis of significant genetic differentiation in P alaemon floridanus populations across the wider Caribbean and Gulf of Mexico. Population level comparisons were conducted using sequences of the mt DNA COI . In agreement with predictions, AMOVA and pairwise F ST values demonstrated population differentiation among most pairs of the studied populations. Only Panama and East Florida populations were genetically similar. An isolation‐with‐migration population divergence model (implemented in IMA 2) indicated that population divergence with incomplete lineage sorting can be invoked as the single mechanism explaining genetic dissimilarity between populations from the east and west coast of Florida. Historical demographic analyses indicated demographic expansion of P. floridanus in some localities [recent in Panama and ancient in East Florida and the wider Caribbean (entire dataset)] but constant population in other localities (in Belize and West Florida). This study rejects the idea of panmixia in marine species with high long‐distance dispersal ability. Contemporary and historical processes might interact in a complex manner to determine current phylogeographic patterns.

Lindane Biodegradation by Defined Consortia of Indigenous Streptomyces Strains - María Soledad Fuentes; Juliana María Sáez; Claudia Susana Benimeli; María Julia Amoroso (Water, Air, & Soil Pollution, 2011)

Understanding carbohydrate-carbohydrate Interactions by means of glyconanotechnology - Jesus M. de la Fuente; Soledad Penadés (Glycoconjugate Journal, 2004)